87. Electromyographic findings in patients with late-onset pompe disease (LOPD). Issue 12 (December 2017) - Marino, M.; Terranova, C.; Rizzo, V.; Musumeci, O.; Rodolico, C.; Girlanda, P.; Toscano, A.
Abstract : Glycogen storage disease II (GSD II), also known as Pompe disease is an autosomal recessive disorder caused by mutations in the GAA gene encoding the enzyme acid alpha-glucosidase. Two different clinical forms have been described: infantile (IOPD) and late-onset (LOPD). Aim of the study is to evaluate EMG findings, in particular distal muscle involvement, in a cohort of LOPD patients. 15 LOPD patients (9 Male–6 Female) underwent to ENG and EMG evaluation looking at spontaneous activity, MUP analysis recruitment. EMG evidenced the presence of myotonic discharges (MD) in paraspinal muscles in 6 patients and in distal limb muscles in 1 patient. Fibrillation potentials occurred in all muscles where MD were found. Short duration, MUPs were found in the paraspinal (6/12), proximal (6/12) and distal limb muscles (5/12). Our results confirm that myopathic EMG pattern is usually observed in proximal muscles, but we also find a similar pattern in distal muscles revealing a subclinical involvement. Moreover, myotonic discharges and denervation activity are present in both paraspinal and distal muscles. We can conclude that it is useful to extend the EMG study also to distal muscles even if not clinically compromised.